Formulação de massas cerâmicas para porcelanas elétricas utilizando resíduos oriundos de corpos de fusíveis - Anunciação, Elenise Barreto Barbosa da (2013)
The power industry generates as waste ceramic bodies of electrical fuses that are discarded after use. The formulation of ceramic bodies for porcelain electrical insulators using waste from the bodies fuse allocation promotes environmentally appropriate, through the reuse of the material. This work evaluated the technical feasibility of using waste for use in electrical porcelains with formulations containing the residue, feldspar and kaolinite. The raw materials were processed through grinding and sieving to 200 mesh. The ceramic material obtained from the proposed formulations with 25%, 30%, 34% and 40% of the residue went through a vibratory mill for grinding and homogenization, and then were sieved at 325 mesh. The samples were shaped in a uniaxial press, with the application of 25 MPa and sintered at 1100° C, 1150°C, 1200°C, 1225°C and 1250°C, at levels of 20 and 45 minutes. Were also developed bodies of evidence with reference formulations obtained without residue, to establish a comparison on physical, mechanical and electrical. The tests were conducted and technology: linear shrinkage, porosity, water absorption, resistance to bending to three points, measuring insulation resistance electrical resistivity of the material, X-ray diffraction and X-ray fluorescence Waste characterizations pointed to the existence of two phases: mullite and quartz phases are of great importance in the microstructure of the ceramic and this fact reveals a possibility for reuse in electrical porcelains. The mullite is an important constituent because it is a phase that makes it possible to increase the mechanical strength in addition to the body allows the use at high temperatures. The use of ceramic bodies residue fuses, proved feasible for application in electrical porcelain and the most significant results were obtained by the formulations with 25% waste and sintering at 1200°C